2004
DOI: 10.1128/iai.72.8.4751-4762.2004
|View full text |Cite
|
Sign up to set email alerts
|

Interaction ofChlamydia trachomatisSerovar L2 with the Host Autophagic Pathway

Abstract: Chlamydiae are obligate intracellular pathogens that replicate within a membrane-bound compartment (the inclusion) and are associated with important human diseases, such as trachoma, pneumonia, and atherosclerosis. We have examined the interaction of the host autophagic pathway with Chlamydia trachomatis serovar L2 by using the specific autophagosomal stain monodansylcadaverine, antibodies to autophagosome-associated markers, and traditionally used autophagic inhibitors, particularly 3-methyladenine and amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 65 publications
4
67
2
Order By: Relevance
“…14 Additionally, a potential role for host autophagy in Chlamydia trachomatis pathogenesis has been proposed. 15 Similar to the results obtained with P.gingivalis, exposing infected cultures to autophagy inhibitors -such as 3-methyladenine and amino acids -altered the inclusion maturation and Chlamydia growth. 15 Work from our own laboratory demonstrated that Coxiella burnetii, a gram-negative bacterium, replicates in a compartment labeled by the autophagosomal protein Atg8/LC3.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…14 Additionally, a potential role for host autophagy in Chlamydia trachomatis pathogenesis has been proposed. 15 Similar to the results obtained with P.gingivalis, exposing infected cultures to autophagy inhibitors -such as 3-methyladenine and amino acids -altered the inclusion maturation and Chlamydia growth. 15 Work from our own laboratory demonstrated that Coxiella burnetii, a gram-negative bacterium, replicates in a compartment labeled by the autophagosomal protein Atg8/LC3.…”
supporting
confidence: 65%
“…15 Similar to the results obtained with P.gingivalis, exposing infected cultures to autophagy inhibitors -such as 3-methyladenine and amino acids -altered the inclusion maturation and Chlamydia growth. 15 Work from our own laboratory demonstrated that Coxiella burnetii, a gram-negative bacterium, replicates in a compartment labeled by the autophagosomal protein Atg8/LC3. 16 Furthermore, we have recently shown that both physiologically and pharmacologically induced autophagy favor the development of the Coxiella replicative vacuole.…”
supporting
confidence: 65%
“…Although in some cases the autophagic response functions as an innate immune response against pathogens like Mycobacterium tuberculosis, 22 Group A Streptococcus 23 and Listeria monocytogenes, 24 in other cases the microorganisms take advantage of this cellular process to favor the infection. [25][26][27] That is the case of Porphyromonas gingivalis, 26,27 Brucella abortus, 27 Coxiella burnetii, 28 Chlamydia 29 and Staphylococcus aureus. 30 The main difference between these two behaviors is not well understood to date, but is important to mention that some pathogens have the faculty to modulate the autophagic response in their own benefit.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy is a major mechanism for degradation and recycling of intracellular macromolecules (Klionsky and Emr, 2000). Although studies have indicated a lack of autophagosomal fusion with the chlamydial inclusion, the intracellular bacteria were sensitive to 3-methyladenine and other traditional inhibitors of autophagy (Al-Younes et al, 2004). The autophagy pathway is thought to intersect MVBs prior to lysosomal delivery (Lucocq and Walker, 1997).…”
Section: Journal Of Cell Science 119 (2)mentioning
confidence: 99%
“…The PI 3-kinase inhibitor 3-methyladenine is also a modulator of autophagy (Seglen and Gordon, 1982); and in the pathogenesis of Chlamydia, a potential role of the host cell's autophagy pathway has been proposed (Al-Younes et al, 2004). Autophagy is a major mechanism for degradation and recycling of intracellular macromolecules (Klionsky and Emr, 2000).…”
Section: Journal Of Cell Science 119 (2)mentioning
confidence: 99%